A Hardware Implementation and Analysis of Testing MPPT Algorithms on PV Modules - Harvie, D.; Rajakaruna, Sumedha (IEEE, 2014)
Maximum Power Point Tracking (MPPT) algorithms are an important part of photovoltaic systems, with a large amount of literature having been published on different approaches and comparisons. Yet there have been very few practical comparisons between the performances of different algorithms published. This work attempted to resolve this by designing and implementing a custom test system with high accuracy and speed to test algorithms in real time at update rates currently being used in industry. The outcome of the research showed difference in the PV modules tested was more significant than the expected difference between algorithms. However the complete test system performed to specification and is now repurposed for use in teaching and other research.